The Destruction of Nature and the Heralds of Brazilian Conservacionism in the First Decades of the Twentieth Century (Revista Brasileira Multidisciplinar, 2008)
This paper aims to present the panorama of the destruction of nature in Brazil during the first decades of twentieth century, and the exponents of Brazilian conservacionism, that positioned themselves against that scenery of carelessness, ignorance and omission. The role and the actions of the main heralds of the struggle against the destruction that was infringed to the natural world are analyzed, specially the relevance of their ideas. Moreover, the first legal measures of the nature conservation in the last century are pointed out.
Keywords: Conservacionism; Destruction of Nature; Brazil; Forests; Twentieth Century.